The Customer Experience Model of Thailand’s Cosmetic Industry - Sakulwongsirichok, Patcharasita; Paopan, Natsapan (Mahachula Academic Journal, 2021)
A study of the customer experience model of the Thailand’s cosmetic industry were a mixed method explanatory research with a quantitative research combined with qualitative research. The objectives of the research were to study the customer experience model of Thailand’s cosmetic industry and factors affecting to the customer experience of Thailand’s cosmetic industry. A questionnaire was used to collect data from the sampling groups of entrepreneurs, executives or managers with marketing strategy roles and responsibilities or managing the brand of the organization in the cosmetic business, totaling 420 samples to analyzing the statistical result by using the analysis of Structural Equation Model (SEM). The results of the quantitative study were also used to create a semi-structured interview tool to verify the model and defined the customer experience model of Thailand’s cosmetic industry. The results of the study showed that from the analysis of confirmatory factor analysis (CFA), the customer experience factors such as inbound marketing, digital marketing, gamification marketing and brand authenticity are positive influences on brand advocacy, and be able to set the customer experience model of the Thailand’s cosmetic industry and has been found the customer experience to be indirectly influenced by other factors.